Spins in nuclear and hadronic reactions : proceedings of the RCNP-TMU Symposium - Yabu, H. (Hiroyuki); Suzuki, T. (Toru); Toki, H. (World Scientific, 2000)
Spin physics is one of the most important and active areas of theoretical/experimental nuclear physics. In nuclear reactions, the observations of spin polarizations give important clues to the nuclear structures and reaction mechanism. For high energy nuclear physics, the polarized quark-parton distributions of the nucleon/nucleus are studied intensively. In the study of baryon structures and nuclear astrophysics, spin is an important observable through hadron reactions. The focus of these proceedings is on the spin-dependent phenomena in nuclear and hadronic reactions and related topics in nuclear and hadron physics. The main subjects covered are: spin polarization phenomena in nuclear and hadronic reactions; spin-dependent excitations in nuclei and spin observables; recent development in nuclear reaction theories; spin-dependent phenomena in fundamental processes; and related topics.